DIAGNOSA PENYAKIT DAN MODEL PERUBAHAN PADA UNIKA SANTO THOMAS MEDAN - Tinambunan, Anitha Paulina (UNIKA Santo Thomas, 2023)
The peak of tough competition and changes in the external environment forces an organizations to be able to adapt and make changes. However, most of organizations do not make changes because they are trapped by their own problems; this study aims to 1) Identify the type of disease experienced by Unika Santo Thomas Medan; 2) Explain the types of changes made by Unika Santo Thomas Medan; 3) Changes in the model of change left by Unika Santo Thomas Medan; 4) Knowing the change diagnosis model applied to Unika Santo Thomas Medan. This research is policy research because the research process is carried out on fundamental issues and the findings can be recommended to decision makers. The research data is secondary data obtained through interviews and documentation techniques. The results of the study show that in the period 1998 - 2015 Unika Santo Thomas Medan presented itself as an